Malacca laws : the effect of islam and customs in the aspect of family law / Zanirah Mustafa@Busu and Intan Nurul ‘Ain Mohd Firdaus Kozako - Mustafa@Busu, Zanirah; Mohd Firdaus Kozako, Intan Nurul ‘Ain (Universiti Teknologi MARA Kelantan, 2019)
Malacca Laws (Hukum Kanun Melaka), is a written law existed during the Malacca Sultanate. It was established as a Malay customary law that is compatible with Islamic law. Malacca Laws is believed to be enacted during the ruling period of Sultan Muhammad Shah (1424-1444 AD) and implemented during the reign of Sultan Muzaffar Shah (1445-1458 AD), and methodically organized during the ruling period of Sultan Mahmud Shah (1489 -1511 AD). Malacca Laws is the first Islamic law that was introduced by Sultan Muhammad Shah in the state of Malacca. Its jurisdictions covered the Malacca state and all territories conquered by Malacca. Malacca Laws which has 44 articles related to ruling power, laws, and taboos of family law, significantly affects the laws of other states. Family aspects in Malacca Laws are discussed in the present study to understand the influence of Islam and customs adopted in the past, in terms of their effects on the family law as well as other laws. Literature search is used in the present study. The objective of this study is to find articles that are related to family aspects contained in the Malacca Laws. The discussion focuses on matters related to marriage, guardianship, and inheritance of property as well as some provisions of the law relating to marriage